Evaluation of Ureteral Jets in Pregnancy by Colour Doppler: Effect of Patients’ Position - Mohammad Wasim Awan, Waqas Yaqub, Saima Ather, Aneela Abid (Journal of Rawalpindi Medical College, 2015)
Background: To determine the frequency of ureteral jets in supine and lateral decubitus position in women of second and third trimester of pregnancy by colour Doppler Methods: In this cross sectional study, healthy women with singleton pregnancy in their second and third trimester and age range between 17 to 36 years were included. Exclusion criteria was subjects having solitary kidney, history of urinary obstruction or previous urological surgery, patients with nephrolithiasis and patients with renal scarring. Grey scale and colour Doppler ultrasonography was performed, with a 3.5 MHz convex probe. Before each examination the procedure was explained to the patient who had to come with full bladder. Doppler ultrasound of bladder area was performed in a transverse plane to include both ureteric orifices to visualize the bilateral ureteral jets. Number of ureteral jets was recorded for a period of one minute in supine position. If the jets were not visualized, the scanning time was extended for three minutes in total. The patient was then asked to adopt right and left lateral decubitus position and number of ureteral jets were recorded for a period of one or three minutes. Right ureteral jets were recorded in left lateral decubitus position whereas left ureteral jets were recorded in the right lateral decubitus position.No. of ureteric jets were analyzed under qualitative variables like patient’s chronological age and gestational age. Descriptive statistics of study included the value of mean, frequency mode and standard deviation of both sets of position. Results: The mean age of patients was 25.09 ± 4.055 years with minimum and maximum 18 and 33 years. Majority (52.08%) were in the age group of 25-30 years.. The average gestation age was 26.02 ± 2.526 weeks with minimum and maximum gestation age 21 and 32 weeks respectively. The mean number of ureteral jets seen in supine position at right side was 1.91 ± 1.71 with minimum and maximum number of jets 0 and 4 respectively. Most frequent (mode) number of jets were “0” in 39 (40.6%) of the patients. Conclusion; Colour Doppler imaging of ureteral jets offers potentially useful information in the assessment of urolithiasis. Nevertheless, urine flow may be altered in pregnancy, simulating ureteral obstruction in some women imaged in the supine position during the second and third trimester of pregnancy.